Measurement of the decays B → φK and B → φK - Aubert, B; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Palano, A; Chen, G; Chen, J; Qi, N; et al. (2001)
An attempt was made to observe B decays to φK+, φK0, φK*+, and φK*0 with significances, including systematic uncertainties, of greater than four standard deviations. It was found that the decay B+ → φπ+ has both Cabibbo-Kobayashi-Maskawa and color suppression relative to φK+.